2016
DOI: 10.1016/j.biombioe.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Balancing biofuel production and biodiversity: Harvesting frequency effects on production and community composition in planted tallgrass prairie

Abstract: Native perennial grasslands have been proposed as a source of feedstocks for the production of second-generation lignocellulosic biofuels in the Midwestern USA. Although the consequences of some management decisions for biomass production and plant community composition are well understood (e.g. fertilization), less is known about the effects of harvesting frequency. We compared a once-and twice-annual harvesting regime at two restored prairies in southwestern Michigan established with identical seed mixtures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 71 publications
1
12
1
Order By: Relevance
“…These results differ from a study of restored populations of Elymus elymoides, where directional selection consistently favored a similar suite of traits in populations located 60 km apart (Kulpa and Leger 2013). The differences we find between Chamaecrista populations could be a direct result of environmental differences between the two sites: despite their close proximity, plant community composition and some abiotic conditions (such as soil nitrogen and water holding capacity) differ (Stahlheber et al 2016), which could generate different selection pressures at each site. Perhaps the original source population was preadapted to site conditions at Marshall but not at Lux.…”
Section: Temporal Variation In Selection and Differences Between Sitescontrasting
confidence: 99%
See 1 more Smart Citation
“…These results differ from a study of restored populations of Elymus elymoides, where directional selection consistently favored a similar suite of traits in populations located 60 km apart (Kulpa and Leger 2013). The differences we find between Chamaecrista populations could be a direct result of environmental differences between the two sites: despite their close proximity, plant community composition and some abiotic conditions (such as soil nitrogen and water holding capacity) differ (Stahlheber et al 2016), which could generate different selection pressures at each site. Perhaps the original source population was preadapted to site conditions at Marshall but not at Lux.…”
Section: Temporal Variation In Selection and Differences Between Sitescontrasting
confidence: 99%
“…In 2010, two former agricultural fields (one 13 ha and one 11 ha) near Kellogg Biological Station in southwest Michigan, Lux Arbor (42°28 0 23″ N, 85°26 0 50″ W) and Marshall (42°26 0 37″ N, 85°18 0 34″ W), were prepared for restoration using identical protocols and were planted with identical prairie seed mixes (containing 19 grass and forb species, including Chamaecrista, seeded at 0.28 kg/ha, roughly 26,700 seeds/ha) as part of a large bioenergy experiment being conducted by the Great Lakes Bioenergy Research Center. Despite being located in close proximity, being prepared in the same manner, and being seeded with the same seed mix, plant community composition and some abiotic conditions (such as soil nitrogen, phosphorus, and water holding capacity) differ between sites (Stahlheber et al 2016). Biomass from each prairie is harvested every year using identical protocols (see Stahlheber et al [2016] for full site details).…”
Section: Study Systemmentioning
confidence: 99%
“…Therefore, the primary advantages of NWSG polycultures over Switchgrass monocultures for biofuel production may be limited to wildlife conservation. Previous studies have observed plant communities among harvest frequencies in conservation grasslands similar to our NWSG plantings (Jungers et al 2015, Stahlheber et al 2016. However, increased cutting frequency can increase light availability, promoting photophilic plant species otherwise deterred by tall vegetation and dense grass canopies (Hautier et al 2009, Wilson andTilman 1991).…”
Section: Discussionsupporting
confidence: 60%
“…data). Therefore, sitepreparation techniques should be explored for marginal land opportunities that can produce grasslands with significant proportions of C 4 grasses for effective ethanol yield (Adler et al 2009, Stahlheber et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…While we find 371 evidence of selection and/or evolutionary responses on all traits measured in the Lux population, 372 there is less evidence of selection on the Marshall population. These differences could be a direct 373 result of environmental differences between the two sites: despite their close proximity, plant 374 community composition and some abiotic conditions (such as soil nitrogen and water holding 375 capacity) differ (Stahlheber et al 2016), which could generate different selection pressures at 376 each site. Alternatively, we may find evidence of past selection in one population but not the 377 other not because of differences in selection pressures, but because of differences in the 378 populations' capacities to respond to selection or the degree to which the populations were 379 preadapted to local site conditions.…”
Section: Conclusion 366mentioning
confidence: 99%